Equal Employment Opportunity Sebagai Upaya Mewujudkan Kesetaraan Kesempatan kerja - Malihah, Lola (Universitas Sang Bumi Ruwa Jurai, 2024)
Getting a decent job and livelihood is the right of all Indonesian citizens guaranteed in the Law. In fact, not a few still experience discrimination in the workplace. Starting from restrictions on promotion, career development to rejection in the recruitment process. Several policies have been implemented starting at the international level, namely the existence of international labor organization (ILO) conventions which are then ratified by each country. In Indonesia, the policy is regulated in the Manpower Law. Equal Employment opportunity is a policy that prioritizes equality in employment opportunities, so that there is no more discrimination caused by differences in race, ethnicity, sex and religion. This paper is a literature review that aims to analyze the role of EEO policies in realizing equal employment opportunities. The data presented is in the form of secondary data obtained from various literature sources such as books, research reports, articles and other scientific publications. These results show that EEO policy is one of the effective efforts to eliminate discrimination and achieve equality in employment opportunities.